Analysis and comparison model for measuring tropospheric scintillation intensity for ku-band frequency in malaysia (2011)
This study has been based on understanding local propagation signal data distribution characteristics and identifying and predicting the overall impact of significant attenuating factors regarding the propagation path such as impaired propagation for a signal being transmitted. Predicting propagation impairment is important for accurate link budgeting, thereby leading to better communication network system designation. This study has thus used sample data for one year concerning beacon satellite operation in Malaysia from April 2008 to April 2009. Data concerning 12GHz frequency (Ku-band) and 40° elevation angle was collected and analysed, obtaining average signal amplitude value, ÷ and also standard deviation ó which is normally measured in dB to obtain long-term scintillation intensity distribution. This analysis showed that scintillation intensity distribution followed Gaussian distribution for long-term data distribution. A prediction model was then selected based on the above; Karasawa,ITU-R, Van de Kamp and Otung models were compared to obtain the best prediction model performance for selected data regarding specific meteorological conditions. This study showed that the Karasawa model had the best performance for predicting scintillation intensity for the selected da ta.